Data Transmission with Improving Lifetime of Cluster Network - et. al., Anitha S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The efficiency of selecting the cluster head plays a major role in resolving the complexities faced in network management aiming to improve the longevity of sensors in the network. The clustering process is followed by selecting proper cluster heads with the consideration of energy conservation among participant nodes. While coming to security concept on WSN, the trust based cluster head selection is significant with the assumption of cooperation of all sensor nodes. In view of this assumption, the traditional methods could not help in defining the ideal cluster head of the network. This work proposes Voronoi Clustered Secure Contextual Cryptographic Algorithm (VC-SCCA) by combining Voronoi method for clustering process and cryptographic algorithm for secure data transmission. This is considered as two-tier architecture whereas, clustering takes place in first tier and encryption along with decryption takes place in the second tier. The proposed algorithm is compared with two state-of-art methods such as, Secured WSN (SeC‐WSN) and Taylor based Cat Salp Swarm Algorithm (Taylor C-SSA) in terms of energy consumption, Packet Delivery Ratio (PDR), network lifetime, encryption time and decryption time. As a result, the proposed VC-SCCA achieves 53.2% of energy consumption, 98.6% of packet delivery ratio, 97.5% of network lifetime, 62.8sec of encryption time and 71.2sec decryption time.